Working with a domestic assessment system to estimate the need of support and care of elderly and disabled persons: results from field studies. (September 2014) - Hein, Andreas; Steen, Enno-Edzard; Thiel, Andreas; Hülsken-Giesler, Manfred; Wist, Thorben; Helmer, Axel; Frenken, Thomas; Isken, Melvin; Schulze, Gisela C.; Remmers, Hartmut
<x xml:space="preserve">Abstract</x> This article describes the results of field studies performed over a period between five months and 24 months. The objectives of these studies were to collect long-term real-life data to evaluate how these data can be mapped to items on standardized assessment tests and which presentation method is most suitable to inform caregivers about critical situations and changes in health or care needs. A Home-monitoring system which uses modern sensor technologies was developed for and used in these field studies. It was installed in living environments of seven people (three who were not in need of care, two in need of care, and two with mental disabilities). The data were generated by sensor data acquisition and questionnaire reporting. Four types of data analysis and representation were evaluated to support caregivers. Results show that sensor data can be used to determine information directly or indirectly, which can be mapped to relevant assessment items and presented with different degrees of granularity. It is also feasible to determine and present additional information of potential interest which cannot be directly mapped to any assessment item. Sensor data can also be displayed in a live view. This live data representation led to a decrease in the caregivers' workload when assessed according to the German version of the Perceived Stress Questionnaire.